Cultural aspects in multicultural mentoring-to-work relationships - Sirppa Kinos; Ilse Van den Berckt; Roza Pambukhchyan; Marja Kiijärvi-Pihkala; Olga Kaartinen; Virve Pirttikoski (International Journal of Evidence Based Coaching and Mentoring, 2023)
This survey analyses mentors’ and migrant mentees’ perceptions of the role that cultural factors have in labour market integration and in the mentoring relationship. The data consists of Webropol surveys and interviews. The findings revealed that cultural similarity, local language proficiency and the ability to build up trust were experienced as supportive. Mentoring can promote cultural competences. We recommend using local languages, recruiting mentors from the same professional field and including the subject ‘culture’ in the mentoring trainings.